Excellent response to secukinumab in an infant with severe generalized pustular psoriasis. Issue 6 (4th February 2021) - López‐Sánchez, Cristina; Falla, Lina María; Roé‐Crespo, Esther; Arostegui, Juan Ignacio; Mozos, Ana; Bernal, Sara; Iznardo, Helena; Baselga‐Torres, Eulalia
Abstract: Generalized pustular psoriasis (GPP) represents the rarest form of psoriasis, which may be potentially fatal. In the last decade, (likely) pathogenic variants in the IL36RN, CARD14 and AP1S3 genes have been associated with monogenic GPP forms. Despite these advances, the genetic basis of most patients with GPP remains unidentified. Treatment of GPP patients is often difficult, with no consensus about the best available options to date. We report herein an infant with severe GPP in whom the disease started at the age of 2 months. Genetic investigations identified a heterozygous pathogenic variant in the IL36RN gene associated with a heterozygous variant of uncertain significance in the CARD14 gene. After previous treatment failures with acitretin, cyclosporin and anakinra, treatment with the interleukin‐17 antagonist secukinumab resulted in a dramatic and prompt positive response that persisted at 12‐month follow up. According to our experience, we believe secukinumab can be an effective and safe treatment for pediatric patients with GPP even before 1 year of age.